Premenstrual dysphoric disorder and its co-existence with depression, anxiety, and stress as risk factors for suicidal ideation and suicide attempts among university students in Bangladesh: A single-site survey - Nitai Roy; Sultan Mahmud Imran; Aysha Siddiky; Samia Sultana; Sumana Mahmud; Rejwana Rashid; Moneerah Mohammad ALmerab; Mohammed A. Mamun (PLoS ONE, 2025)
Background Premenstrual Syndrome (PMS) and Premenstrual Dysphoric Disorder (PMDD) have been identified as potential risk factors for various mental health issues, such as suicidal ideation and attempts. However, few studies have examined this association among Bangladeshi university students. This study aimed to examine the potential associations between PMDD and its co-existence with depression, anxiety, stress, and various suicidal behaviors, including suicidal ideation and attempts. Methods A cross-sectional survey involving 516 university students was conducted between September and October 2023. The survey was carried out in person and employed a structured questionnaire that comprised demographic information; the Depression, Anxiety, and Stress Scale (DASS-21); and the Premenstrual Symptoms Screening Tool (PSST), a 19-item screening tool for premenstrual symptoms. Multivariable logistic regression analyses were conducted to examine the relationships between variables. Results In the present study, participants with PMDD reported a prevalence of 38.8% for past-year suicidal ideation and 28.6% for suicide attempts. Through logistic regression analysis, we found a significant association between moderate/severe PMS and PMDD and a higher likelihoods of reporting suicidal ideation (AOR =  4.73; 95% CI 2.08–10.73 and AOR =  5.42; 95% CI 2.02–10.52) and suicide attempts (AOR =  3.77; 95% CI 1.36–10.50 and AOR =  4.07; 95% CI 1.22–15.56). The association between suicidal behaviors and PMS/PMDD was mediated by co-existing conditions such as depression, anxiety, and stress. Conclusions A notable proportion of individuals diagnosed with PMDD reported experiencing suicidal ideation or engaging in suicide attempts at some point in their lives. The findings of this research support the importance of conducting regular assessments of suicidal risk among women experiencing moderate to severe premenstrual disturbance. Furthermore, it is crucial to integrate mental health screenings and implement psychosocial interventions specifically designed for women diagnosed with PMS or PMDD and those with co-existing depression, anxiety, and stress alongside PMS/PMDD.